Wavelet Transform Application Based on Matlab Simulation - Tan, Nguyen Minh; Chen, Hua-Ming; Duong Giap, Binh; Nhat, Hoang Le Quang (VNU Journal of Science: Mathematics - Physics; Vol 36 No 1DO - 10.25073/2588-1124/vnumap.4459, 2020)
Multiple Input Multiple Output (MIMO) and Orthogonal Frequency Division Multiplexing (OFDM) are two combined technologies to provide the spectral efficiency and high data rate required for 4G, 5G wireless systems. Discrete Wavelet Transform (DWT) is presented as an alternative for Fast Fourier Transform (FFT) since there is no necessity for Cyclic Prefix (CP) due to the overlapping properties of DWT. By a simple replacement of the FFT with DWT in MIMO OFDM system, an improvement of performances has been detected which leads to a new system scenario DWT-based MIMO-OFDM. In this thesis, such a system is simulated and the performance of Bit Error Rate (BER) is analyzed to determine the different types of wavelets in various channel condition with different modulations (4, 16, 64 -QAM). Therefore, DWT-based MIMO-OFDM in comparison with DFT-based MIMO-OFDM system was investigated using MATLAB simulation software. And besides, I would like to refer to use Neural Network algorithms to replace Wavelet transform in the next research.